2019
DOI: 10.1080/15384101.2019.1593645
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Down-regulated LAMA4 inhibits oxidative stress-induced apoptosis of retinal ganglion cells through the MAPK signaling pathway in rats with glaucoma

Abstract: Glaucoma is a neurodegenerative disorder that is generally accepted as the main cause of vision loss. In this study, we tested the hypothesis that laminin α4 (LAMA4) is implicated in glaucoma development by controlling apoptosis of retinal ganglion cells (RGCs) through the mitogenactivated protein kinase (MAPK) signaling pathway. Expression profiles and genes associated with glaucoma were searched to determine the objective gene. Intraocular pressure (IOP) rats model were established and IOP was measured. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Under oxidative stress conditions, sirtuin 3 (SIRT3) impairment reduces the activity of superoxide dismutase 2 (SOD2) and increases ROS production [ 49 , 50 ], and multiple mitogen-activated protein kinases (MAPKs) signaling pathways such as p38 and extracellular signal-regulated kinase 1/2 (ERK1/2) are activated [ 51 , 52 ]. Thus, we tested whether AIBP regulates expression levels of SIRT3 and SOD2, as well as p38 and ERK1/2 activation in WT and naïve Apoa1bp −/- mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under oxidative stress conditions, sirtuin 3 (SIRT3) impairment reduces the activity of superoxide dismutase 2 (SOD2) and increases ROS production [ 49 , 50 ], and multiple mitogen-activated protein kinases (MAPKs) signaling pathways such as p38 and extracellular signal-regulated kinase 1/2 (ERK1/2) are activated [ 51 , 52 ]. Thus, we tested whether AIBP regulates expression levels of SIRT3 and SOD2, as well as p38 and ERK1/2 activation in WT and naïve Apoa1bp −/- mice.…”
Section: Resultsmentioning
confidence: 99%
“…8 , SIRT3 and SOD2 are widely expressed in the retina, consistent with previous studies [ 19 , 77 , 78 ], and AIBP may contribute to SIRT3-SOD2-mediated protection of retinal structure and cells against oxidative stress. Under oxidative stress conditions, multiple MAPK signaling pathways, including p38 and ERK1/2, are activated [ 51 , 52 ]. Our study demonstrated that loss of AIBP persistently increased phosphorylation of p38 and ERK1/2 in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, water-dispersible hesperetin was shown to protect RGCs by decreasing I/R-induced ROS [ 221 ]. Furthermore, Wang et al have reported that laminin α4 (LAMA4) is involved in the development of glaucoma and that downregulation of LAMA4 might reduce ROS-induced apoptosis of RGCs by inhibiting the activation of the MAPK signaling pathway [ 222 ]. In another study, neurotrophins (NTs) were shown to be promising agents for neuroprotection activated by NT signaling through Trk receptors by the PI3-K-Akt-TOR and the MEK/ERK1/2/MAP kinase pathways, evoking protective and cell survival responses in the retina [ 223 ].…”
Section: Therapeutic Strategies To Reduce Oxidative Stressmentioning
confidence: 99%
“…There are over a million RGCs in the eyes, classified according to different physiological, morphological, and molecular criteria [105]. RGCs represent one of the central cell types damaged in many ocular neurodegenerative diseases, characterized by oxidative stress, such as diabetic retinopathy [106,107], glaucoma [108,109], and retinal ischemia-reperfusion injury [110,111]. It has been proved that oxidative stress plays a pivotal role in the loss of RGCs in several eye diseases.…”
Section: Oxidative Damage Of Retinal Ganglion Cellsmentioning
confidence: 99%